Art in book form infographics, book forms, interviews, design. (SendPoints Publishing Co., Ltd., 2018)
"Opposite to the prediction of its fall in recent years, physical books, by virtue of its particular "five senses" for readers, unexpectedly remained its popularity. Echoing this circumstance, ART IN BOOK FORM is born, as an anthem for physical books. It shares with you book design philosophy of Lu Jingren (the Chinese book design master) and Stefan Sagmeister (the design rockstar) and Hubert & Fischer. The book also "unfolds" the history of book form in detail in front of you, in a more visual way, explaining both historical and modern book formats with diagrams and real pictures. A selection of modern book designs is featured to enhance your understanding."--The publisher.